2014
DOI: 10.3928/23258160-20140306-06
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Complications of Pneumatic Retinopexy Over a 12-Year Period

Abstract: Pneumatic retinopexy remains a reasonably successful option in the management of primary retinal detachment. No difference in best corrected visual acuity outcomes in eyes achieving SOS versus those requiring additional surgery was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
(31 reference statements)
0
7
1
Order By: Relevance
“…Previous studies have reported new retinal breaks and PVR following PR as single surgery in 11.7% and 5% of cases, respectively (Chan CK, 2008). In a study with 12 years follow up, 30% of RRD cases developed new breaks after management with PR (Modi YS et al, 2014). The PVR rate in our study was much lower than 40% reported by Dhami et al (Dhami A et al, 2018).…”
Section: Resultscontrasting
confidence: 57%
“…Previous studies have reported new retinal breaks and PVR following PR as single surgery in 11.7% and 5% of cases, respectively (Chan CK, 2008). In a study with 12 years follow up, 30% of RRD cases developed new breaks after management with PR (Modi YS et al, 2014). The PVR rate in our study was much lower than 40% reported by Dhami et al (Dhami A et al, 2018).…”
Section: Resultscontrasting
confidence: 57%
“…30 Previous reports have analyzed predictive factors for successful visual and anatomical outcomes in large multicenter 2 and tertiary hospitals in which study cohorts are composed of patients who underwent PR by one of multiple possible surgeons. 12,27,28,[30][31][32][33] However, there has been no previous long-term study on PR involving a single surgeon. By incorporating multiple surgeons, more data can be collected and analyzed, but this may also introduce variability in surgical technique.…”
Section: Introductionmentioning
confidence: 99%
“…Later, authors have found it to vary between 60% and 82%. [ 7 8 9 10 11 12 ] Table 5 lists the major studies and their results of PR. Our SOSR of 60% is toward the lower side due to the inherent biases in a retrospective study and uncontrolled parameters.…”
Section: Discussionmentioning
confidence: 99%